"All Say He is a Downright Methodist": The Ministry and Evangelical Loyalism of the Rev. William Stringer - Tirenin, Gregory (Church history, 2024)
William Stringer was at various times a cheesemonger, a Methodist lay preacher, a priest, and an American Loyalist exile. Originally from London, Stringer preached the Gospel for the early Methodist movement, but longed for priestly ordination in the Church of England. Unable to achieve this goal due to his humble background, he was instead ordained in 1764 by the controversial and ecumenically minded Greek Orthodox bishop, Gerasimos Avontilies (also known as Erasmus of Arcadia), who ordained several Methodists under Greek Orthodox rites in London. Having acquired illicit ordination, Stringer moved to Philadelphia where he ministered to a parish that had broken from the Church of England during the Great Awakening. The clergy of Philadelphia responded negatively and wrote to Archbishop Richard Terrick of London, who ordered Stringer to desist from his ministry. However, Stringer did such a remarkable job of bringing his congregation back into the Anglican fold that Terrick agreed to re-ordain him in London under Anglican rites in 1773. With the outbreak of the American Revolution in 1775, Stringer supported the British cause and rejected the revolt as inconsistent with Christian obedience. He was forced to leave America and return to England, where he lived out the rest of his life as a curate. Despite his initial transgressions, I argue that Stringer was a force for order, stability, and orthodoxy in a revolutionary world.